NEPHROPROTECTIVE ACTIVITY OF THE ETHNOMEDICINAL PLANTS CAESALPINIA BONDUC AND MOMORDICA DIOICA FROM NE INDIA AGAINST CISPLATIN INDUCED CHEMOTHERAPEUTIC TOXICITY - Talukdar, Anindita; Kalita, Ranjan Dutta; Gohain, Nilakshi; Saikia, Kandarpa Kr.; Kalita, Mohan Chandra (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: Cisplatin a potent anticancer drug is used for treatment against different forms of cancer. However a major limitation of cisplatin is its nephrotoxicity and severe side effects. The main objective of the present study was to investigate the nephroprotective activity of the medicinal plants Caesalpinia bonduc and Momordica dioica against cisplatin-induced nephrotoxicity. Methods: In the present study wistar rat models were intraperitoneally injected with cisplatin for eight consecutive days Plant extracts of different compositions were administered for eight days after injection of cisplatin. The polyphenolic content of the crude extracts was investigated using the Folin Ciocalteau method while the flavonoid estimation was carried out using the aluminium chloride method. The antioxidant activities of the extracts were assayed using the DPPH radical scavenging method. Plant extracts were tested for their nephroprotective ability using modified Berthelot method, uricase method, alkaline picrate method. Results: In the present study it was found that the level of creatinine, urea, uric acid and blood urea nitrogen was lowered by the crude hexane extract of Momordica dioica and ethyl acetate extract of Caesalpinia bonduc as compared to the control group. The total phenolic content and the total flavonoid content was found to be highest in the hexane extract of Momordica dioica with 110.51±1.0 μg/GAE and 1.92±0.15 μg/QE. The methanol extract of Caesalpinia bonduc was found to be the highest in inhibition of the DPPH free radicals with nearly 80% inhibition. Conclusion: The present study revealed the nephroprotective ability of the hexane extract of Momordica dioica and ethyl acetate extract Caeselpinia bonduc. The extracts were also found to have higher antioxidant activity and therefore their nephroprotective activity might be due to attenuation of oxidative stress.